2007
DOI: 10.1007/s00431-006-0411-x
|View full text |Cite
|
Sign up to set email alerts
|

Bullying behaviours and psychosocial health: results from a cross-sectional survey among high school students in Istanbul, Turkey

Abstract: The aim of this study was to investigate bullying behaviours and their associations with health and health risk behaviours. This study involved completion of the Health Behaviour in School-Aged Children (HBSC) and Youth Self Report (YSR) questionnaires by 3,519 students. Of the students, 59.4% (n=2,091) were neither bullies/nor victims, 22% (n=774) victims, 9.4% (n=331) bully/victims and 9.2% (n=323) bullies. Generally, students involved in bullying behaviours were more likely to have higher YSR scale scores t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
65
3
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 42 publications
9
65
3
13
Order By: Relevance
“…Findings of various studies show that the rates of peer bullying, victimization, and being both victim and bully vary between 7.6-18.8%, 9.3-22.0% and 6.4-9.4%, respectively. 6,[39][40][41] It was found that the prevalence values obtained from this study are consistent with other study data.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Findings of various studies show that the rates of peer bullying, victimization, and being both victim and bully vary between 7.6-18.8%, 9.3-22.0% and 6.4-9.4%, respectively. 6,[39][40][41] It was found that the prevalence values obtained from this study are consistent with other study data.…”
Section: Discussionsupporting
confidence: 89%
“…Although there is no compromise of the relationship between bullying and victimization and parental education, it is stated that tendency toward bullying decreases with an increase in the education of the parents, while those students whose mothers have a lower education engage in bullying more. 6 Moreover, literature surveys showed that bullying is observed with more frequency among elementary school students, but it is reported that the rate of engaging in such behaviors and victimization decreases as the students grow older. 4,9,16,50 The findings from this study showed that the frequency of bullying in all groups is lower with respect to elementary school students, and bullying behaviors can be seen in all age groups-especially among 10th grade students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Fu et al (2013) found that adolescents from families with lower SEL were more frequently victims of severe bullying behaviours but the relation was reversed in the case of less severe behaviours. However, other investigations have not found any relation between SEL and being a victim of face-to-face bullying (Barboza et al, 2009;Fernández-Tomé, 2015;García-Continente et al, 2010;Magklara et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…Gençler, eriflkin döneme geçifl sürecinde pek çok zorlukla bafl etmek zorunda kal›rlar ve sa¤l›kl› olmalar› onlar›n zorluklarla etkin bir flekilde bafl edebilmelerini kolaylaflt›r›r. Ancak, araflt›rmalar, ergenlerin madde kullan›m›, diyet yapma, ö¤ün atlama, besin de¤eri yüksek yiyecekler yerine enerjisi yo¤un yiyecekleri tüketme, yeterince fiziksel etkinlikte bulunmama, düzenli difl f›rçalamama ve zorbal›k gibi pek çok sa¤l›¤› riske atan davran›fllar nedeni ile sa¤l›k-lar›n› k›sa ya da uzun sürede riske att›klar›n› göstermekte-dir (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Giriflunclassified